2023
DOI: 10.1002/cam4.6036
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of increased preoperative red cell distribution width (RDW) and changes in RDW for colorectal cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the present study, we showed that the RDW level was higher in the group with liver metastasis than in the group without liver metastasis after colon cancer surgery. This result is consistent with the findings of Lu et al [ 28 ]. These results suggest that preoperative RDW has a certain predictive value for postoperative liver metastasis in colon cancer.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we showed that the RDW level was higher in the group with liver metastasis than in the group without liver metastasis after colon cancer surgery. This result is consistent with the findings of Lu et al [ 28 ]. These results suggest that preoperative RDW has a certain predictive value for postoperative liver metastasis in colon cancer.…”
Section: Discussionsupporting
confidence: 94%
“…This suggests high RDW predicts poorer ICI response. Other studies demonstrate similar connections between high pre-treatment RDW and worse cancer prognosis, including colorectal and metastatic renal cell carcinomas [ 24 , 25 ]. As with these studies, our research suggests that high RDW values are associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 63%
“…Warwick et al examined the data of 917 patients who underwent surgery for non-small-cell lung carcinoma and confirmed that a preoperative RDW-CV of >15.3% was a significant risk factor for postoperative death ( P = 0.001) and survival ( P = 0.0001) [ 24 ]. In colorectal cancer, a high RDW level (≥13.5%) was reported as an additional separate indicator of both cause-specific survival (CSS) and OS [ 25 ], with a significant reduction in 10-year OS among patients with high RDW [ 26 ]. These studies all suggest that RDW is an important biomarker for cancer.…”
Section: Discussionmentioning
confidence: 99%